Monitoring and control of processes using a network of PLCS - Rajarama Rao Chandukudlu (2008)
In the recent years PLC's (Programmable Logic Controller) handle more tasks and its existence in every single industry is becoming a reality. These industries have started to integrate the entire process by networking controllers and connecting it to a central control station for managing the processes using the latest automation technologies that are available in the market. These automation software are generally expensive due to their advanced built-in features. The small and medium scale industries seldom make use of these features and are interested in cost effective automation software to reduce the operating cost and stay competitive in the market.